Clinical and pharmacokinetic drug evaluation of delafloxacin for the treatment of acute bacterial skin and skin structure infections. (2nd November 2017) - Bassetti, Matteo; Pecori, Davide; Cojutti, Piergiorgio; Righi, Elda; Pea, Federico
ABSTRACT: Introduction : In the era of multi-drug resistant pathogens, the adequate treatment of skin and skin structure infections remains a challenge for clinicians. Delafloxacin, with its broad spectrum against Gram-positive, Gram-negative and anaerobic organisms, represents a new therapeutic option in this setting, especially when coverage of methicillin-resistant Staphylococcus aureus is required in the empirical or targeted approach. Areas covered : In this drug evaluation, the Authors have reviewed the pharmacokinetic and pharmacodynamic characteristics of delafloxacin. In addition, recent data on clinical efficacy and safety from clinical trials have been included. Expert opinion : Delafloxacin represents an attractive therapeutic option due to a broad antimicrobial and favorable pharmacokinetic and pharmacodynamic profile. Several in vitro studies have demonstrated the low potential for resistance selection if used in empirical regimens. Delafloxacin is a promising candidate for the treatment of Gram-positive infections, especially if co-infection with other pathogens is suspected. This is because of the very low MIC of the agent for Gram-positive (including MRSA) and anaerobic bacteria and because of the wide spectrum of activity against Gram-negative organisms. For these interesting microbiological and PK/PD characteristics we expect future uses of this drug in other indications such as diabetic foot infection, osteomyelitis, prosthetic joint infections, abdominal infections and central nervous system infections.